PREVALENCE AND RISK FACTORS OF WORK-RELATED MUSCULOSKELETAL DISORDERS AMONG WORKERS IN HIGH-VOLTAGE TRANSMISSION LINE NETWORK AND SUBSTATIONS - Andonov, Goran; Stoleski, Sasho; Mijakoski, Dragan; Minov, Jordan; Panajotovikj Radevska, Maja; Karadzinska Bislimovska, Jovanka (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Introduction: There is a high risk of developing work-related musculoskeletal disorders (WMSDs) among workers in high-voltage transmission line network and substations. Most WMSDs are cumulative disorders resulting from repeated exposure to one or more harmful factors over a long period of time. Aim of the Study: The aim of this study is to determine the occurrence and frequency of symptoms of WMSDs among workers in high-voltage transmission line network and substations. Material and Methods: This cross-sectional study involves 100 workers from a high-voltage transmission line network and substations, all males aged 20 to 63, classified as electricians – group F06, electricians – group F07 and substation workers. The research methodology includes a standardized questionnaire “Symptoms Survey for Work-Related Musculoskeletal Disorders (WMSDs)”. The results obtained are statistically processed by descriptive and analytical methods. Results: The frequency of symptoms of WMSDs among workers from a high-voltage transmission line network and substations that lasted two or more days in the last year, and was caused by their work is 32% and it refers to pain or discomfort in any region. The most common localizations are determined on the lower back (14%), knee (11%) and shoulder (9%). No upper back pain was registered in any of the subjects. A significantly higher number of electricians reported that their working body position was combined compared to substation workers, and that they often had to reach further from their body compared to substation workers. On the other hand, a significantly higher number of substation workers declared that they do not reach beyond their body compared to electricians. There is no significant difference between substation workers and electricians in terms of performing repetitive movements. Conclusion: WMSDs are often regularly occurring among workers in high-voltage transmission line network and substations; therefore, it underlines the need for their early detection through preventive medical examinations and application of appropriate measures for protection of workers.
Keywords: electricians; electrical industry; musculoskeletal disorders; power lines; preventive measures; substations; substation workers; work capacity